2020
DOI: 10.1002/aenm.202000927
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom Doping: An Effective Way to Boost Sodium Ion Storage

Abstract: In response to the change of energy landscape, sodium‐ion batteries (SIBs) are becoming one of the most promising power sources for the post‐lithium‐ion battery (LIB) era due to the cheap and abundant nature of sodium, and similar electrochemical properties to LIBs. The electrochemical performance of electrode materials for SIBs is closely bound up with their crystal structures and intrinsic electronic/ionic states. Apart from nanoscale design and conductive composite strategies, heteroatom doping is another e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
205
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 371 publications
(229 citation statements)
references
References 307 publications
2
205
1
Order By: Relevance
“…From experimental evidence, it has also been observed that extrinsic oxygen defects can arise as a consequence of nitrogen doping. [ 68 ] In this section, we investigate two nitrogen‐ and oxygen‐containing defects, the N C O C and N C 2O C defects ( Figure ). These defects are geometrically similar to the 2O C and 3O C defects, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…From experimental evidence, it has also been observed that extrinsic oxygen defects can arise as a consequence of nitrogen doping. [ 68 ] In this section, we investigate two nitrogen‐ and oxygen‐containing defects, the N C O C and N C 2O C defects ( Figure ). These defects are geometrically similar to the 2O C and 3O C defects, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21] However, metal oxides and metal sulfides show poor intrinsic electronic conductivity, and thereby lead to compromised power/energy performance. [22,23] Meanwhile, metal nitride, typically vanadium nitride (VN), has been demonstrated to realize both high energy/power density in view of its high electrical conductivity (1.67 × 10 6 S m −1 ), wide potential window (1.0-1.2 V), and superior electrochemical redox reactivity. [24] With the help of nanoscale design, various VN nanostructures (such as nanosheets, nanorods, nanowires, nanoflowers) have been explored and boosted electrochemical kinetics and utilization are verified in these systems due to larger surface area and increased active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Heteroatom doping is a widely used technique in altering the chemical and physical properties of carbon such as porosity, conductivity, wettability and capacitance [111–112] . It involves the substitution of carbon with a heteroatom (N, P, S, B, etc.)…”
Section: Development Of Carbon‐based CDI Electrodesmentioning
confidence: 99%
“…These examples show that heteroatom doping can produce multiple effects even with single and/or multiple dopants. Nitrogen doping seems to be the popular dopant of choice not just with CDI but also with energy storage devices [112] . However, it is evident that more can be explored in this area such as using other dopants like fluorine, or other dopant combinations to create synergistic effects on the properties of carbon.…”
Section: Development Of Carbon‐based CDI Electrodesmentioning
confidence: 99%